The Application of Chemical Castration as Additional Punishment for the Perpetrators of Child Sexual Violence Crimes Subject to the Death Penalty - Rumondor, Nova Ernny (KnE Social Sciences, 2024)
Human life is a cyclical pattern, commencing with birth and childhood, progressing through adolescence and young maturity, entering adulthood, and ultimately reaching old age. From these periods, childhood is a crucial time that requires full attention, as children are often incapable of defending and protecting themselves. This lack of self-protectiom is specifically observed against the heinous crimes of sexual violence, where the perpetrators are sentenced to the death penalty or chemical castration as additional punishment. Therefore, this study aims to analyze the application of chemical castration as additional punishment for the perpetrators of a child sexual violence crimes. In this context, a normative juridical method was used to emphasize the patterns by which the application of the rule governing the imposition of castration process is implemented in Decision Number 86/Pid.Sus/2022/PT Bdg. The implementation patterns of restitution and protection for the child victims of sexual violence are also explored. The results showed the following conclusions, firstly, the application of the rule governing the imposition of chemical castration as additional punishment for the perpetrators of the sexual crimes was fair when the defendant was subject to the death penalty. However, castration process was unnecessary due to causing excessive criminal sanctions, as the death penalty was the highest sanction according to Article 67 of the Criminal Code. Secondly, the implementation of restitution and protection for the child victims became a negative precedent and failed to develop a deterrent effect when imposed on the state. In this case, the perpetrators were often comfortable due to being unburdened with compensating the victims through restitution, increasing the level of sexual violence crimes. This situation hindered the achievement of protecting and preventing crimes. From these results, Decision Number 86/Pid.Sus/2022/PT Bdg was appropriate in meeting the sense of justice for the victims and facilitating their recovery. Keywords: Child; Sexual Violence Crimes; Death Penalty; Chemical Castration.